Idiopathic Pulmonary Fibrosis With Emphysema: Evidence of Synergy Among Emphysema and Idiopathic Pulmonary Fibrosis in Smokers. - Mitchell, Patrick D.; Das, Jeeban P.; Murphy, David J.; Keane, Michael P.; Donnelly, Seamas C.; Dodd, Jonathan D.; Butler, Marcus W. (Respiratory Care, 2015)
BACKGROUND: Emphysema and fibrosis, typically the idiopathic pulmonary fibrosis (IPF) form of usual interstitial pneumonia (UIP), can co-exist as combined pulmonary fibrosis emphysema (CPFE). It is unknown whether there is a pathobiologic basis for CPFE beyond the coexistence of fibrosis and emphysema. The aim of this study was to ascertain radiologic differences in severity of fibrosis and emphysema in smokers with IPF versus other forms of UIP. METHODS: Computed tomography thorax images were prospectively rescored in retrospectively identified smokers (minimum 5-pack-year history) with radiologic UIP (any etiology). Radiologic severity (emphysema/fibrosis/reticulation) was scored in consensus by two radiologists, blinded to clinical details, across 5 lung regional levels, and then correlated with clinical data. RESULTS: For the whole cohort (IPF, n = 102; non-IPF UIP [mainly rheumatoid arthritis/asbestosis/scleroderma], n = 30), IPF and non-IPF UIP smokers were similar regarding pack-year, age, gender, and lung function (P > .1). IPF smokers had greater whole lung fibrosis and reticulation scores (P < .04 in all cases). CPFE was present in n = 61 (IPF, n = 49; non-IPF UIP, n = 12). Compared with smokers with non-IPF CPFE, smokers with IPF and emphysema (IPFE) were similar regarding confounders (P > .1). There were significantly greater regional reticulation severity (P = .009), cumulative emphysema severity (P = .04), and cumulative reticulation severity (P <.001) scores in IPFE versus non-IPF CPFE. CONCLUSIONS: When controlled for confounders, smokers with IPFE have worse radiologic CPFE than other smokers with non-IPF UIP and emphysema, suggesting an interactive synergy among IPF, emphysema, and smoking, with more extensive emphysema due to either inherent susceptibility and/or traction effects. IPFE should be considered separately from other CPFE in future work. It is currently unknown whether CPFE is a distinct pathobiologic entity; therefore, we identified subjects with radiologic UIP (any etiology) who had been similarly exposed to smoke, and asked whether there are differences in the extent/severity of radiologic fibrosis and/or emphysema in those with IPF versus individuals with non-IPF UIP. Although relevant confounders were similar, IPF smokers had greater whole lung fibrosis and reticulation scores than smokers with secondary forms of UIP, and in the CPFE subgroup, smokers with IPF/emphysema had worse radiologic CPFE findings than smokers with non-IPF UIP/emphysema. It is shown for the first time that relevant confounding variables do not explain the observed excess radiologic severity of emphysema and fibrosis in smokers with IPF compared with smokers with non-IPF UIP, lending support to the hypothesis that there is a pathobiologic mechanism or synergy involved in IPF with emphysema that is distinct from the mere co-existence of UIP and emphysematous processes.